Optimization of the Near Miss Reporting System in Achieving Zero Accidents at PTPN IV ADOLINA Garden (SIRISKA Online Smart Application) - Umi Salmah; Sri Malem Indirawati; Risanti FR Situmorang; Pauzi Ibrahim Nainggolan (Universitas Respati Yogyakarta, 2023)
A large number of accidents begins with the number of near misses and the magnitude of work risks experienced by workers, so control efforts are needed as early as possible. This study uses quantitative research using the SIRISKA smart online application (Occupational Risk Mapping System) involving sections clerks and oil palm harvesters as respondents. There were 3 cases of work accidents, and there was a near-miss hazard at each stage of oil palm harvesting. The near-miss hazards that can occur are being cut by an sickle or an axe, falling by an sickle, being crushed by a frond, being hit by a fibre, or being pierced by a palm thorn which must be recorded and reported. By optimizing the reporting system using the SIRISKA smart online application, it is hoped that zero accidents can be achieved at PTPN IV Adolina Garden.